A comparison of the effect of different nickel⁃titanium instruments combined with ultrasonic irrigation on root canal preparation - ZHANG Xiaowei; LIANG Jingping; RAN Shujun (口腔疾病防治, 2019)
Objective To compare the removal efficiency and the amounts of apically extruded debris using Twist⁃ ed File (TF), Twisted File Adaptive (TFA), ProTaper, and ProTaper Next combined with ultrasonic irrigation and to pro⁃ vide an experimental basis for the selection of root canal instrumentation in the clinic. Methods Forty mandibular pre⁃ molars were randomly divided into 4 groups (n＝10 teeth per group). The canals were cut using a Twisted File, Twisted File Adaptive, ProTaper, or ProTaper Next nickel⁃titanium instrument. The canals were irrigated with ultrasonic irriga⁃ tion. The apically extruded debris were collected in preweighted Eppendorf tubes. The amount of dental tissue removed and extruded debris were assessed with an electronic balance. Results The amount of tooth tissue removed in groups A, B, C and D was 20.5 ± 2.0 mg, 17.8 ± 4.2 mg, 20.8 ± 3.9 mg and 16.5 ± 2.2 mg, respectively. Combined with ultra⁃ sonic irrigation, the Twisted File and ProTaper had a better removal efficiency than the ProTaper Next(P < 0.05). There was no significant difference in the amount of extruded debris (χ2＝4.057, P＝0.255) among four groups. Conclusion The Twisted File and ProTaper had a better removal efficiency than the ProTaper Next combined with ultrasonic irriga⁃tion. There was no significant difference in the amount of extruded debris using four Nickel⁃titanium instruments com⁃ bined with ultrasonic irrigation.